Adverse Experiences in Childhood and Sexually Transmitted Infection Risk From Adolescence Into Adulthood. Issue 9 (September 2017) - London, Stephanie; Quinn, Kelly; Scheidell, Joy D.; Frueh, B. Christopher; Khan, Maria R.
Abstract : Background: Childhood maltreatment, particularly sexual abuse, has been found to be associated with sexual risk behaviors later in life. We aimed to evaluate associations between a broad range of childhood traumas and sexual risk behaviors from adolescence into adulthood. Methods: Using data from Waves I, III and IV of the National Longitudinal Study of Adolescent to Adult Health (Add Health), we used logistic regression to estimate the unadjusted odds ratio (OR) and adjusted OR (AOR) for associations between 9 childhood traumas and a cumulative trauma score and three sexual risk outcomes (multiple partnerships, sex trade involvement, and sexually transmitted infection [STI]) in adolescence, young adulthood, and adulthood. We also examined modification of these associations by gender. Results: Associations between cumulative trauma score and sexual risk outcomes existed at all waves, though were strongest during adolescence. Dose-response–like relationships were observed during at least 1 wave of the study for each outcome. Violence exposures were strong independent correlates of adolescent sexual risk outcomes. Parental binge drinking was the only trauma associated with biologically confirmed infection in young adulthood (AOR, 1.46; 95% confidence interval [CI], 1.01–2.11), whereas parental incarceration was the trauma most strongly associated with self-reported STI in adulthood (AOR, 1.70; 95% CI, 1.11–2.58). A strong connection was also found between sexual abuse and sex trade in the young adulthood period (AOR, 2.17; 95% CI, 1.43–2.49). Conclusions: A broad range of traumas are independent correlates of sex risk behavior and STI, with increasing trauma level linked to increasing odds of sexual risk outcomes. The results underscore the need to consider trauma history in STI screening and prevention strategies. Abstract : A nationally representative study found that a broad range of childhood traumas are associated with sexual risk behavior and sexually transmitted infection from adolescence into adulthood.